Background Information About Heat Treatment of Metals - Mamataliyeva Zulfiyakhon Khusanovna (Zien Journals, 2022)
This source provides general information about the process associated with heating and cooling metals and alloys to make the necessary changes in their structure and properties. The process can also involve deformation and chemical and magnetic effects. Information is given about the phases formed in the heat treatment of metals and their known properties. explains certain parts of some properties and possibilities of heat treatment of metals. For example, Annealing, stress relieving, and heating for homogenization or annealing with phase transformations
Keywords: Annealing; treatment of metals; cementation; homogenization